Dementia Prevention Self-Management in Older Thai Adults with Type 2 Diabetes: Development and Psychometric Properties of Two Questionnaires - Noppamas Pipatpiboon; Jirapas Sripetchwandee; Eakachai Kantawong; Ruksanudt Budda; Daniel Bressington (Nursing Reports)
Background/Objectives: The prevalence of dementia, a complication of uncontrolled type 2 diabetes (T2DM), is rising among older adults. Effective self-management for dementia prevention is essential, but no validated questionnaires currently exist to evaluate these behaviors. Methods: The Dementia Preventive Individual and Family Self-Management Process Questionnaire (DP-IFSM-PQ) and the Dementia Preventive Self-Management Behavior Questionnaire (DPSMBQ) were developed based on the Individual and Family Self-Management Theory to evaluate dementia prevention self-management behaviors in older adults with T2DM. Items for the DP-IFSM-PQ (30 items) and DPSMBQ (29 items) were generated through literature review and tested for face validity. A quantitative cross-sectional study evaluated their psychometric properties using exploratory factor analysis (EFA) (n = 311) and confirmatory factor analysis (CFA) (n = 254). Results: The final DP-IFSM-PQ comprises four factors and 29 items, showing acceptable fit with limited discriminant validity. The DPSMBQ includes seven factors and 27 items, demonstrating good fit and acceptable discriminant validity. Conclusions: The Thai-language DP-IFSM-PQ and DPSMBQ show reasonable psychometric properties for application in Thai older adults, but revisions of certain items and further studies are recommended to reassess their properties.